Pendampingan Pemanfaatan Teknologi Informasi Komunikasi (TIK) Sebagai Media Pendukung Pembelajaran Bagi Guru di SDN 1 Sabaru Kota Palangka Raya - sundari sundari; Sri Rohaetin; Liling Lenlioni; Dhebby Novianty; Margaretha Siska Oktarina (Jurnal Pengabdian Kampus, 2022)
The world of education is currently experiencing significant changes, especially these changes in the field of information technology. This has an impact on the shifting of the learning process that is applied to the world of education which was originally manual in nature but is now slowly developing towards digital. The aim of national education is to improve the quality of quality human resources. Utilization of ICT is needed to carry out interactive and innovative teaching and learning activities. The problem faced by SDN-1 Sabaru Palangka Raya City is that teachers are expected to be able to adapt to existing technological developments in the current digital era by continuing to update their competencies so that they can keep abreast of current technological developments in the industrial era 4.0 towards Towards an Era of Society 5.0. But there are still many teachers who have not utilized ICT media in teaching. Solutions to overcome the problems faced by partners are (1) Carry out mentoring activities in order to increase knowledge and skills in making digital learning media utilizing technology with visual displays and images that attract students' interest in taking lessons and helping teachers to support teaching and learning activities. (2) Carry out training and practice for teachers on the management of ICT-based learning, and developing the use of ICT and being able to design practical and innovative ICT-Based Teaching Materials.